DESIGN AND CONSTRUCTION OF RICE HUSK COMBUSTION WITH USED FUEL OIL CAPACITY 5KG - naufal kurnia karim (Dinamika : Jurnal Ilmiah Teknik Mesin, 2022)
Rice husk is an agricultural commodity produced from the rice milling industry which generally exists in rural areas. The rice milling industry in Indonesia is able to process more than 40 million tons of unhulled rice into milled rice with a yield of 66-80%. If this condition continues in accordance with its capacity, there will be husks that have the potential of 8 million tons. The waste from rice milling is a potential energy source that can be used as a mixture of rub ash for making bricks and cement, fertilizer and fuel for cooking using a husk furnace. Until now, the development of husk furnaces is still being studied further in various aspects so that the results are much better.Seeing this condition, rice husk waste and used oil that are disposed of for nothing without being accompanied by waste processing have the potential to be used for the manufacture of processing products to become husk charcoal and briquette products whose used oil is used as fuel. Research on the design of rice husk and used oil burning furnaces is also designed to be very environmentally friendly. Therefore, this research is very important because in addition to the product from husk, namely husk charcoal from burning rice, it is quite economical in addition to being briquettes, husk charcoal can also be used as a planting medium.This study aims to determine the design model and mechanism of a rice husk burning stove that utilizes rice husk waste and used oil as fuel. The results of observations for burning 5 kg of dry rice husks in 38 minutes the average temperature reaches 520oC, the burning rate is 2.27 kg/hour, while burning 5kg wet rice husk takes 57 minutes and the burning rate is 2.47 kg/hour. With the design of the rice husk burning stove, it produces an efficiency of 78.47%. Keyword : Rice Husk, Used Oil, Temperature, And Combustion Furnace.